2021
DOI: 10.2147/cmar.s336892
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Predicting Overall Survival in Patients with FIGO II to III Squamous Cell Cervical Carcinoma Under Radical Radiotherapy: A Retrospective Analysis Based on 2018 FIGO Staging

Abstract: Purpose To present a nomogram to predict overall survival in patients with FIGO-2018 II to III squamous cell cervical carcinoma undergoing radical radiotherapy. Patients and Methods Patients diagnosed with FIGO-2018 II to III squamous cell cervical cancer between December 2013 and December 2014 were analyzed retrospectively. The optimal cutoff point for tumor length and width were determined by R package. We identified prognostic factors by univariate and multivariate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Three important factors were selected, including baseline hemoglobin level, primary tumor volume (GTV_P), and body V 5. The final multivariable Cox-pH model constructed using these important factors had prediction performance (C-index: 0.78, 95%CI: 0.73–0.81) better than previous studies [ 25 27 ]. It indicated that the addition of DVH parameters to clinical factors in the model improved the prediction ability for OS.…”
Section: Discussioncontrasting
confidence: 55%
“…Three important factors were selected, including baseline hemoglobin level, primary tumor volume (GTV_P), and body V 5. The final multivariable Cox-pH model constructed using these important factors had prediction performance (C-index: 0.78, 95%CI: 0.73–0.81) better than previous studies [ 25 27 ]. It indicated that the addition of DVH parameters to clinical factors in the model improved the prediction ability for OS.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, we compared FIGO staging and the nomograms with respect to their net benefit. FIGO stage is widely used clinically, and the use of a nomogram could reduce the diversity due to different treatments and sociodemographic statuses when predicting the prognosis of patients with CC ( 25 , 32 ). We found that the nomograms had greater net benefit than the FIGO stage according to DCA and CIC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many studies developed nomograms for diagnosis and prognostic prediction in patients with CC; however, these studies had many limitations, including insufficient sample size (7), the model having a low C-index and prediction accuracy (6,32), insufficient inclusion and exclusion criteria (6,33), and a single study endpoint (8,9). To our knowledge, compared with other studies evaluating CC survival using nomograms (6)(7)(8)(9), the present study considered more real-time sample data and a more complete set of patient prognostic factors (13) than previous studies, showed excellent predictive accuracy for OS and CSS (6)(7)(8)(9)33), and demonstrated greater clinical net benefit.…”
Section: Discussionmentioning
confidence: 99%
“…When predicting the prognosis of patients with CC, the FIGO stage is frequently employed therapeutically, and the adoption of a nomogram could reduce the diversity caused by various treatments and socio-demographic statuses [ 44 ]. In our study, as the FIGO stage for outpatients increased, the survival time decreased.…”
Section: Discussionmentioning
confidence: 99%